Phyto‐fabricated silver nanoparticles inducing microbial cell death via reactive oxygen species‐mediated membrane damage - L. Srinivas Naik; Ch. Venkata Ramana Devi (IET Nanobiotechnology)
Abstract Eco‐friendly synthesis of the silver nanoparticles (AgNPs) has a number of advantages like simplicity, biocompatibility, low toxicity in nature over their physical and chemical methods. In the present study, the authors report biosynthesized AgNPs using the root extract of the perennial plant ‘Spiny gourd’ (Momordica dioica) and investigated their anti‐bacterial application with mechanistic approaches. Different biophysical techniques such as UV‐Vis spectroscopy, FTIR, XRD, TEM, SAED, and DLS were employed for AgNPs characterization. The synthesized AgNPs were polydispersed, crystalline in nature, with anionic surface (−22.3 mV), spherical in shape with an average size of 13.2 nm. In addition, the AgNPs were stable in room temperature and in different biological buffers. The anti‐bacterial activities of AgNPs were studied with respect to the pathogens such as Bacillus subtilis, Staphylococcus aureus (Gram‐positive), Pseudomonas aeruginosa, Escherichia coli, Klebsiella planticola (Gram‐negative), and Candida albicans. Also, mechanistic studies of AgNPs such as protein leakage assay, nucleic acid leakage assay, ATP leakage assay, ROS accumulation, determination of biofilm degrading activity, measurement of potassium, showing that the synthesized AgNPs are capable of containing a potential application in the antimicrobial therapeutic agents and the pharmaceutical industry.